Comparison of a direct aspiration first pass technique vs. stent retriever thrombectomy for the treatment of acute large vessel occlusion stroke in the anterior circulation with atrial fibrillation - Fan, Hongxing; Li, Zhenhui; Li, Yi; Tan, Yanping; Mao, Zhenlin; Liu, Qian; Zhu, Youfeng (Frontiers in Neurology, 2023)
Objectives The stent retriever thrombectomy (SRT) and a direct aspiration first-pass technique (ADAPT) are the two main mechanical thrombectomy (MT) techniques for acute ischemic stroke. Few data are available for comparing the therapeutic effects associated with the two mechanical thrombectomy techniques in acute ischemic stroke with atrial fibrillation. The purpose of this study was to compare the efficacy and safety of both techniques for the treatment of acute large vessel occlusion stroke in the anterior circulation with atrial fibrillation. Methods Retrospective analysis was performed in stroke patients with atrial fibrillation admitted to Guangzhou Red Cross Hospital from January 2018 to June 2022 who received mechanical thrombectomy by either SRT or ADAPT. Comparisons were made with regards to the initial traits, course of therapy, effectiveness indicators, and complications of these individuals. The primary outcome is recanalization rate. Results In this study, after screening 431 patients, 92 eligible patients, with 48 patients received SRT and 44 patients received ADAPT, were included. There was no significant difference in the recanalization rate between the two groups (SRT 87.5% vs. ADAPT 84.1%, P = 0.639). Compared with SRT, patients in ADAPT group had a shorter puncture to recanalization time [33.5 min (27.0–59.5) vs. 50.5 min (31.5–91.5), P = 0.009], a higher first pass success recanalization rate (54.5 vs. 33.3%, p = 0.040), and a higher rate of patients with improvement of NIHSS scores ≥4 at discharge (84.1 vs. 56.3%, P = 0.004). However, distal embolization occurred more frequently in the ADAPT group than that in SRT group (50.0 vs. 22.9%, P = 0.007). There was no significant difference between the two groups in the 3-month mRS score, symptomatic cerebral hemorrhage, or mortality. Conclusions Compared with SRT, ADAPT has similar recanalization rate for the treatment of acute large vessel occlusion stroke in the anterior circulation with atrial fibrillation. However, ADAPT might be more effective in terms of shorter puncture to recanalization time and higher first pass success recanalization rate. Further studies are needed for confirming our results.